Scale for coping strategies for informal caregivers of patients with cancer - Sagrario Espinoza-Salgado, Fatima; Reyes-Lagunes, Isabel; Velasco-Rojano, Eduardo; Bravo-González, María Cristina; Ramírez Ramírez, Armando (Psicooncología, 2017)
Objective: Analize the psychometric properties of a new instrument valid and reliable instrument, which assesses the coping strategies in informal primary caregivers (IPC) of patients with cancer. The Instrument of Coping Strategies in Primary Informal Caregivers (IEECPI), consists in 2 factors (Emotion- Focused) and 3 indicators (Problem-Focused). Method: Has been evaluated 20 IPC cancer patients with a questionnaire of open questions, to get information about the conceptualization of the theoretical dimensions of the coping strategies, been getting 216 indicators, that were grouped in two categories: Focused emotion and Focused problem, of which 55 reagents that were applied to 255 IPC were generated. Once the data proposed by Nunnally and Bernstein (1994) y el de Reyes-Lagunes, García y Barragán (2008) procedure is followed: frequency analysis of each item, to determine the predominant type of distribution, discrimination and directionality item, starting reliability, correlation analysis, factor analysis and full and reliability factors. Results: The results show that the 55 items at the begging, after statistical analysis, finally 15 items divided into two factors (Appraisal Focused strategies to the avoidant emotion and focused to the negative emotion emotional) and 3 indicators (Focused- problem were obtained focused problem positive and negative cognitive, appraisal cognitive). Conclusion: The IEECPI, it is a valid, reliable and culturally relevant to evaluate coping strategies in ICP of cancer patients and identify needs of intervention instrument.